2017
DOI: 10.1177/1940082917717051
|View full text |Cite
|
Sign up to set email alerts
|

Small Protected Areas as Stepping-Stones for Jaguars in Western Mexico

Abstract: The jaguar (Panthera onca) is one of the most endangered felids in the world. Its distribution has been reduced by 50% globally, and the species continues to be hunted illegally. We provide data on jaguar abundance, sex ratio, seasonal and daily activity, and site fidelity in La Papalota-a 368-ha natural protected area in Nayarit, western Mexico. La Papalota is located between two areas with high priority for the conservation of the jaguar: Marismas Nacionales Biosphere Reserve and the San Blas-San Juan area. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Currently, both species still have relatively high population sizes in large forest fragments of difficult access, low human presence, and with some degree of protection (e. g., Los Chimalapas and Sierra Norte in Oaxaca, Sierra Madre de Chiapas and Lacandona in Chiapas, Calakmul in Campeche and Sian Ka'an in Quintana Roo ;Naranjo 2009;Chávez-Tovar et al 2016;Botello et al 2017). However, Chávez-Tovar et al (2016) and Luja et al (2017) indicated that jaguars may occur in unprotected or highly fragmented sites with human impact. Also, the two species play important roles in the ecosystem; tapirs are important herbivores and seed dispersers of various plant species (Naranjo 2009), and jaguars are the largest predators in the Neotropics (Chávez-Tovar et al 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, both species still have relatively high population sizes in large forest fragments of difficult access, low human presence, and with some degree of protection (e. g., Los Chimalapas and Sierra Norte in Oaxaca, Sierra Madre de Chiapas and Lacandona in Chiapas, Calakmul in Campeche and Sian Ka'an in Quintana Roo ;Naranjo 2009;Chávez-Tovar et al 2016;Botello et al 2017). However, Chávez-Tovar et al (2016) and Luja et al (2017) indicated that jaguars may occur in unprotected or highly fragmented sites with human impact. Also, the two species play important roles in the ecosystem; tapirs are important herbivores and seed dispersers of various plant species (Naranjo 2009), and jaguars are the largest predators in the Neotropics (Chávez-Tovar et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the size of the fragment where station 1 was set (> 10,000 ha, including secondary and old forest). We believe that this fragment can either work as a biological corridor or as a stepping-stone habitat (Luja et al 2017), where jaguars can be established temporarily or even permanently. During our survey we abundantly recorded three main jaguar preys, the nine-banded armadillo (Dasypus novemcinctus), whitenosed coati (Nasua narica) and the collared peccary (Pecari tajacu; Chávez-Tovar et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Because our study integrates across many species with varying body sizes and home ranges, we set a conservative cut-off of 5 km 2 . We do not wish to diminish the importance of small protected areas, and understand they are important as refuges 37 and act as corridors for species with large home ranges 38,39 . In addition, our analyses do not account for the fact that many species have seasonal distributions, requiring them to migrate between different locations using corridors.…”
Section: Methodsmentioning
confidence: 99%
“…The climate is warm and humid, with a mean annual temperature of 31.7 °C, and the predominant native vegetation comprises mangroves Avicennia germinans and Conocarpus erectus with patches of deciduous forests. Other land use includes secondary vegetation, farmland and livestock pastures (Luja et al, 2017).
Fig.
…”
Section: Study Areamentioning
confidence: 99%